Preparation method and application of aluminum-doped Cu9S5 electrode material

Through the preparation of aluminum-doped Cu9S5 electrode material, the problem of low Al3+ mobility in aqueous aluminum ion batteries is solved, the electrochemical kinetics and cyclic stability of the battery are improved, and higher capacity and rate performance are achieved.

CN119683672APending Publication Date: 2025-03-25BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411894151.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In aqueous aluminum ion batteries, the high charge density and large radius of Al3+ lead to a decrease in mobility, which in turn leads to a collapse in the structure of the positive electrode material, limiting the performance of the battery.

Method used

Aluminum-doped Cu9S5 electrode material was used to prepare CuAl-LDH precursor by hydrothermal and solvent-thermal vulcanization, and Al-Cu9S5 material was obtained by vulcanization treatment, which improved the electronic structure and electrical conductivity of the material.

Benefits of technology

It improves the electrochemical kinetics, capacity and rate performance of the battery, enhances the cycle stability, and is suitable as an electrode material for aqueous aluminum ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005201296700000011
    Figure HDA0005201296700000011
  • Figure HDA0005201296700000021
    Figure HDA0005201296700000021
  • Figure HDA0005201296700000031
    Figure HDA0005201296700000031
Patent Text Reader

Abstract

The invention provides a preparation method and application of an aluminum-doped Cu9S5 electrode material. The chemical formula of the prepared aluminum-doped Cu9S5 material is shown as Al-Cu9S5, and the mass percentage content of the Al element is 1.57-4.77%; the material is of a spherical structure, and the diameter of the material is 20-50 nanometers. The preparation method comprises the following steps: dissolving copper nitrate, aluminum nitrate and urea in water to form a mixed solution, and carrying out hydrothermal treatment to obtain CuAl-LDH precursor powder; and uniformly dispersing the obtained CuAl-LDH precursor powder in an ethylene glycol solution of sodium sulfide, carrying out heating vulcanization reaction to generate Al-Cu9S5, and carrying out filtering, cleaning and vacuum drying to obtain a target product. The battery prepared by taking the Al-Cu9S5 as the positive electrode has relatively high capacity and excellent rate capability, and is suitable for being applied to the water-based aluminum ion battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of positive electrode materials for aqueous aluminum ion batteries, and in particular to an Al-Cu9S5 electrode material and a preparation method thereof. The material is mainly used as a positive electrode material for aqueous aluminum ion batteries. Background Art

[0002] Aqueous aluminum-ion batteries (AAIBs) have attracted widespread attention in the field of energy storage due to their high abundance, high capacity, low cost and high safety. However, the relatively negative reduction potential of Al (-1.67V vs. standard hydrogen electrode (SHE)) causes hydrogen evolution reaction on the anode side of the battery during charging, which greatly limits the application of Al anode in aqueous electrolytes. The inert electrode potential of copper has aroused people's interest in the exploration and optimization of battery systems. Due to the high electrode potential of the copper anode (0.34Vvs.SHE), almost no side reactions occur in aqueous solution. Our team discovered for the first time an aqueous aluminum-ion battery with Cu as anode and LiCl+CuCl+AlCl3 aqueous solution as electrolyte. This battery combines the advantages of dual ion insertion / extraction, making it a relatively ideal battery system. As mentioned in reference 1, Journal of Materials Chemistry A, 2014, 2, 1721-1731, reference 2, Dalton Trans, 2019, 48, 6337-6340, however, Al 3+ High charge density (364C mm -3 ), the hydrated ion radius is large There is a large internal electrostatic force between the Al 3+ The mobility decreases, which leads to the collapse of the cathode material structure. This poses a major scientific challenge to aqueous aluminum-ion batteries.

[0003] Cu 2-x S (x = 1-2) is considered to be a promising material due to its abundant resources and multivalent states. 2- x S has more electrons to participate in the electrochemical reaction, so it can obtain a higher capacity. 2-x S electrode materials usually suffer from sluggish electrochemical kinetics and low cycling stability. To address this problem, cation doping / substitution is a promising approach to effectively tune the properties of metal sulfides, such as Na +, Sn, Zn. According to document 3, Materials Today Energy, 2022, 24, 100940, iron-doped nickel selenide nanosheets derived from NiFe layered double hydroxide (NiFe-LDH) were used as the positive electrode material for aqueous aluminum ion batteries. Due to the combination of the advantages of short ion diffusion distance and high conductivity, the battery with this material as the positive electrode achieves excellent electrochemical performance. Our research group has found that when CuS is used as the positive electrode of an aqueous aluminum ion battery, the battery has good performance, as shown in document 1, Journal of Materials Chemistry A, 2014, 2, 1721-1731, document 2, Dalton Trans, 2019, 48, 6337-6340. However, its electrochemical kinetics are slow and the mechanism is unclear. By using CuAl layered double hydroxide (CuAl-LDH) as a precursor to prepare CuS by sulfidation 2-x S's method is expected to prepare aqueous aluminum ion battery positive electrode materials with excellent performance through the structural advantages of the precursor and precise control of the sulfurization process, thereby improving the overall performance of the battery. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an aluminum-doped Cu9S5 electrode material, which can be used as an electrode material for aqueous aluminum ion batteries and has the advantages of improving electrode conductivity, improving battery electrochemical kinetics, and enhancing battery capacity and rate performance.

[0005] The aluminum-doped Cu9S5 material of the present invention has a chemical formula of Al-Cu9S5, wherein the mass percentage of the Al element is 1.57-4.77%. The material has a spherical structure and a diameter of 20-50 nanometers.

[0006] The preparation method of the aluminum-doped Cu9S5 electrode material of the present invention comprises the following specific preparation steps:

[0007] A. Dissolve copper nitrate, aluminum nitrate and urea in water to form a mixed solution; transfer to a closed reactor, react at 100-120°C for 11-13 hours, filter, wash the obtained sample with deionized water until neutral, and dry to obtain the precursor of Al-Cu9S5, whose chemical expression is CuAl-LDH.

[0008] The molar ratio of copper nitrate to aluminum nitrate in the mixed solution is 3:2-3:1, the molar ratio of urea to copper nitrate is 4:3, and the molar concentration of urea is 0.2 mol / L.

[0009] B. Disperse sodium sulfide evenly in ethylene glycol, the molar concentration of sodium sulfide is 0.1 mol / L. Then disperse the precursor powder obtained in step A in the ethylene glycol solution of sodium sulfide at a ratio of 300-500 ml per gram. Maintain constant temperature at 55°C for 5-20 minutes, filter, rinse the sample with deionized water until it is neutral, and then dry it under vacuum conditions for 6-12 hours to obtain aluminum-doped copper pentasulfide material, whose chemical formula is Al-Cu9S5, in which the mass percentage of Al element is 1.57% to 4.77%. The material has a spherical structure with a diameter of 20-50 nanometers.

[0010] The present invention is characterized in that: a CuAl-LDH precursor powder is prepared by a hydrothermal method in step A, which is in the shape of a spherical flower with a diameter ranging from 7 to 10 microns, and an Al-Cu9S5 sphere is obtained during the sulfurization process in step B. Through the precise synthesis of the CuAl-LDH precursor and the precise control of the sulfurization process, the prepared Al-Cu9S5 has high purity and good particle uniformity, which is beneficial to improving the electrochemical performance of the battery. At the same time, the doping of Al improves the electronic structure of Cu9S5, and Al-Cu9S5 has a larger interlayer spacing and higher electronic conductivity, providing a fast ion / charge migration channel, thereby enhancing the kinetics during the cycle process. The electrode material has excellent performance. Therefore, the material is suitable for use as an electrode material for an aqueous aluminum ion battery.

[0011] Characterization and application experiments

[0012] Figure 1 This is a scanning electron microscope (SEM) characterization of the precursor obtained in step A of Example 1. As can be seen from the figure, the CuAl-LDH is in the shape of a spherical flower with a diameter ranging from 7 to 10 microns.

[0013] Figure 2 This is a scanning electron microscope (SEM) characterization of the Al-Cu9S5 obtained in step B of Example 1. As can be seen from the figure, the Al-Cu9S5 is a sphere with a diameter ranging from 20 to 50 nanometers.

[0014] Figure 3 It is the X-ray diffraction (XRD) diagram of the two materials obtained in steps A and B in Example 1. As can be seen from curve a, the CuAl-LDH precursor synthesized by the hydrothermal method has the characteristic diffraction peak of the LDH material. As can be seen from curve b, the diffraction peak of the sample completely corresponds to the Cu9S5 standard phase (PCPDF#47-1748). By comparing the two curves a and b, it is shown that after the solvent thermal vulcanization treatment, CuAl-LDH is successfully converted into Al-Cu9S5.

[0015] Figure 4: is an X-ray photoelectron spectroscopy (XPS) diagram of the material obtained in step B of Example 1. The diagram shows that the binding energy of Al 2s, corresponding to the +3 oxidation state of Al, is 120.4 eV, proving the successful doping of Al.

[0016] Figure 5-9 The electrode material to be tested is made into an electrode and assembled into an aqueous aluminum ion battery for performance testing.

[0017] Preparation of working electrode: 2 mg of electrode material, 15-20 μL of 5% binder (Nafion solution) and 1 ml of ethanol were mixed thoroughly and coated on a 1×1 cm 2 The surface of titanium foil is dried to obtain the positive electrode. The loading amount of Al-Cu9S5 is 2mg / cm 2 According to the method of patent CN114204138B, Al-Cu9S5 was used as the positive electrode to prepare an aqueous aluminum ion soft pack battery for electrochemical performance testing.

[0018] Figure 5 This is a cyclic voltammetry (CV) curve of an aqueous aluminum ion battery assembled with Al-Cu9S5 and Cu9S5 without aluminum doping obtained in Example 1 as positive electrodes, tested at a scan rate of 10mv / s. Voltage range: between 0 and 1V.

[0019] As can be seen from the figure, the figures enclosed by curves a and b both show obvious redox peaks. At the same time, compared with the figure enclosed by curve b, the area enclosed by curve a is larger, indicating that aluminum doping helps to improve the electrochemical properties of Cu9S5 materials and make Al-Cu9S5 materials have higher capacity.

[0020] Figure 6 The aqueous aluminum ion battery assembled with Al-Cu9S5 obtained in Example 1 and Cu9S5 without aluminum as the positive electrode was charged at 500 mA g -1 The constant current charge and discharge (GCD) curve tested under the current density, the voltage range is between 0 and 1V.

[0021] At 500mA g -1 At a current density of 2.3 Å, the Cu9S5 electrode capacity is 223 mA g -1 , while the Al-Cu9S5 electrode capacity is 463 mA g -1 The capacities of the above two materials clearly show that aluminum doping can significantly improve the storage capacity of the material, which is consistent with the CV test results. -1 At the current density, 79% of the capacity is still maintained, indicating that the Al-Cu9S5 material has excellent rate performance.

[0022] Figure 7 The EIS curves of aqueous aluminum ion batteries assembled with Al-Cu9S5 obtained in Example 1 and Cu9S5 without aluminum doping as positive electrodes are shown in the figure. According to the image, the semicircle value of the Al-Cu9S5 material curve is smaller in the high frequency region, indicating that it has a smaller diffusion resistance. Therefore, aluminum doping helps to reduce the impedance value and improve the conductivity of Cu9S5.

[0023] Figure 8 The contact angle test of the electrodes prepared by using Al-Cu9S5 and Cu9S5 without aluminum doping obtained in Example 1 in LiCuAl electrolyte is used to characterize the wettability of the electrode material. The smaller the contact angle, the higher the wettability. As can be seen from the figure, the contact angle of Cu9S5 without aluminum doping is 81.8°, and the contact angle of Al-Cu9S5 is 58.9°. Compared with Cu9S5 without aluminum doping, the contact angle of Al-Cu9S5 electrode is smaller, the wettability is higher, and it is easier to contact with the electrolyte, thereby improving the electrochemical performance.

[0024] Fig. 9 The Al-Cu9S5 material obtained in Example 2, Example 3 and Example 4 is used as the positive electrode of the aqueous aluminum ion battery assembled at 1000mA g -1 The constant current charge and discharge (GCD) curve tested at a current density of 250 mA g -1 The capacity of Al-Cu9S5 represented by curve b is 370mA g -1 The capacity of Al-Cu9S5 represented by curve c is about 183 mA g -1 This indicates that the Al-Cu9S5 prepared by this method has good electrochemical properties.

[0025] Beneficial effects of the present invention:

[0026] Al-Cu9S5 is solvent-thermally vulcanized on the basis of CuAl-LDH by using hydrothermal and solvent-thermal vulcanization methods. The method is simple and fast to prepare with low cost. In addition, due to the doping of aluminum, Cu9S5 obtains more excellent performance. By controlling the amount and time of sulfur source and precursor, the purpose of controlling the doping amount of aluminum element can be achieved. Due to the structural advantages of the material and the synergistic advantages of metal ion doping, the electrode material has good rate performance and excellent battery capacity. Therefore, the aqueous aluminum ion battery assembled with the material as the positive electrode has the advantages of high specific capacity, good cycle stability, low cost and environmental friendliness. The material has wide application value in the positive electrode material of aqueous aluminum ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The SEM characterization of the CuAl-LDH precursor obtained in step A of Example 1. (a) and (b) are at different magnifications.

[0028] Figure 2 The scanning electron microscope (SEM) characterization of Al-Cu9S5 obtained in step B of Example 1. (a) and (b) are at different magnifications.

[0029] Figure 3 It is the X-ray diffraction (XRD) diagram of the materials obtained in step A and step B in Example 1, wherein a is the material in step A and b is the material in step B.

[0030] Figure 4 This is the X-ray photoelectron spectrum (XPS) of the Al-Cu9S5 material obtained in step B of Example 1.

[0031] Figure 5 The cyclic voltammetry (CV) curves of an aqueous aluminum ion battery tested using the Al-Cu9S5 material obtained in Example 1 and the Cu9S5 material not doped with aluminum as the positive electrode, respectively; wherein a is the Al-Cu9S5 material obtained in step B, and b is the Cu9S5 material not doped with aluminum.

[0032] Figure 6 The constant current charge-discharge (GCD) curves of an aqueous aluminum ion battery in which the Al-Cu9S5 material obtained in Example 1 and the Cu9S5 material not doped with aluminum are assembled as the positive electrode are shown in FIG. a. The Al-Cu9S5 material obtained in step B and b. the Cu9S5 material not doped with aluminum.

[0033] Figure 7 The electrochemical impedance spectroscopy (EIS) curves of aqueous aluminum ion batteries in which the Al-Cu9S5 material obtained in Example 1 and the Cu9S5 material not doped with aluminum are assembled as the positive electrode are shown in FIG. a. The Al-Cu9S5 material obtained in step B and b. the Cu9S5 material not doped with aluminum.

[0034] Figure 8 The contact angle test is a test of the electrode prepared by Al-Cu9S5 obtained in Example 1 and Cu9S5 without aluminum doping. Wherein a is the Al-Cu9S5 material obtained in step B, and b is the Cu9S5 material without aluminum doping.

[0035] Fig. 9The Al-Cu9S5 materials obtained in Example 2, Example 3 and Example 4 are respectively the constant current charge-discharge (GCD) curves of the aqueous aluminum ion battery tested with the positive electrode assembled; wherein a is the Al-Cu9S5 material obtained in step B of Example 2, b is the Al-Cu9S5 material obtained in step B of Example 3, and c is the Al-Cu9S5 material obtained in step B of Example 4. DETAILED DESCRIPTION

[0036] Example 1

[0037] A. Dissolve 9mmol copper nitrate, 4.5mmol aluminum nitrate and 12mmol urea in 60ml water to form a mixed solution; transfer to a closed reactor, react at 110℃ for 12h, wash the obtained sample with deionized water until neutral, and dry to obtain a precursor;

[0038] B. Take 100 mg of the precursor obtained in step A, evenly disperse it in 0.1 mol / L sodium sulfide ethylene glycol solution (30 ml), and keep it at a constant temperature of 55°C in a water bath for 10 minutes; filter, wash the sample with deionized water until it is neutral, and vacuum dry it for 6 hours to obtain Al-Cu9S5 material. The aluminum content in Al-Cu9S5 is determined by ICP-OES, and the mass percentage of Al element is 3.07%.

[0039] Table 1 X-ray photoelectron spectroscopy results of Ta / Cu7S4 materials

[0040] element Mass percentage﹪ Al 3.07

[0041] Example 2

[0042] A. Dissolve 9mmol copper nitrate, 6mmol aluminum nitrate and 12mmol urea in 60ml water to form a mixed solution; transfer to a closed reactor, react at 100℃ for 13h, filter, wash the filter cake with deionized water until neutral, and dry to obtain a precursor powder;

[0043] B. Take 80 mg of the precursor obtained in step A, evenly disperse it in 0.1 mol / L sodium sulfide ethylene glycol solution (30 ml), keep it at a constant temperature of 55°C in a water bath for 5 minutes; filter, wash the sample with deionized water until it is neutral, and vacuum dry it for 10 hours to obtain Al-Cu9S5 material. ICP-OES is used to determine the aluminum content in Al-Cu9S5, where the mass percentage of Al element is 4.77%.

[0044] Example 3

[0045] A. Dissolve 9mmol copper nitrate, 4.5mmol aluminum nitrate and 12mmol urea in 60ml water to form a mixed solution; transfer to a closed reactor, react at 110℃ for 12h, filter, wash the filter cake with deionized water until neutral, and dry to obtain a precursor powder;

[0046] B. Take 100 mg of the precursor obtained in step A, evenly disperse it in 0.1 mol / L sodium sulfide ethylene glycol solution (30 ml), keep it at a constant temperature of 55°C in a water bath for 15 minutes; filter, wash the sample with deionized water until it is neutral, and vacuum dry it for 12 hours to obtain Al-Cu9S5 material. ICP-OES is used to determine the aluminum content in Al-Cu9S5, and the mass percentage of Al element is 2.08%.

[0047] Example 4

[0048] A. Dissolve 9mmol copper nitrate, 3mmol aluminum nitrate and 12mmol urea in 60ml water to form a mixed solution; transfer to a closed reactor, react at 120℃ for 11h, filter, wash the filter cake with deionized water until neutral, and dry to obtain a precursor powder;

[0049] B. Take 60 mg of the precursor obtained in step A, evenly disperse it in 0.1 mol / L sodium sulfide ethylene glycol solution (30 ml), keep it at a constant temperature of 55°C in a water bath for 20 minutes; filter, wash the sample with deionized water until it is neutral, and vacuum dry it for 8 hours to obtain Al-Cu9S5 material. The aluminum content in Al-Cu9S5 is determined by ICP-OES, and the mass percentage of Al element is 1.57%.

Claims

1. A method for preparing aluminum-doped Cu9S5 material, characterized in that: Prepare according to the following specific steps: A. Dissolve copper nitrate, aluminum nitrate and urea in water to form a mixed solution; transfer to a closed reactor, react at 100-120°C for 11-13 hours, filter, wash the obtained sample with deionized water until neutral, and dry to obtain the precursor of Al-Cu9S5, whose chemical expression is CuAl-LDH; The molar ratio of copper nitrate to aluminum nitrate in the mixed solution is 3:2-3:1, the molar ratio of urea to copper nitrate is 4:3; the molar concentration of urea is 0.2 mol / L; B. Evenly disperse sodium sulfide in ethylene glycol to obtain an ethylene glycol solution of sodium sulfide, wherein the molar concentration of sodium sulfide is 0.1 mol / L; then disperse the precursor obtained in step A in the ethylene glycol solution of sodium sulfide at a ratio of 300 to 500 ml per gram; maintain a constant temperature at 55° C. for 5 to 20 minutes, filter, rinse the sample with deionized water to neutrality, and then dry it under vacuum conditions for 6 to 12 hours to obtain an aluminum-doped copper pentasulfide material, whose chemical formula is Al-Cu9S5.

2. The aluminum-doped Cu9S5 material prepared by the method of claim 1 is characterized in that: The chemical formula of the material is Al-Cu9S5, wherein the mass percentage of Al element is 1.57% to 4.77%. The material has a spherical structure and a diameter of 20 to 50 nanometers.

3. The application of the aluminum-doped Cu9S5 material according to claim 2, characterized in that The material is used as the positive electrode material of aqueous aluminum ion batteries.